Life as a guide to prebiotic nucleotide synthesis - Stuart A. Harrison (Nature Portfolio, 2018)
Abstract Synthesis of activated nucleotides has been accomplished under ‘prebiotically plausible’ conditions, but bears little resemblance to the chemistry of life as we know it. Here we argue that life is an indispensable guide to its own origins.